Special fluorine-containing soluble polyimide adhesive for lithium battery as well as preparation method and application of special fluorine-containing soluble polyimide adhesive
By using fluorine-containing soluble polyimide adhesive material, the problems of electrode structure damage and bond failure caused by volume changes in silicon negative electrode materials in lithium-ion batteries are solved, and higher cycling performance and rate performance are achieved.
Patent Information
- Application Number
- CN202411533709.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-31
- Publication Date
- 2025-02-18
AI Technical Summary
The silicon negative electrode material in lithium-ion batteries causes damage to the electrode structure and failure of bonding due to volume expansion and contraction, which in turn affects the energy density and cycle life of the battery.
Fluorinated soluble polyimide (PI) adhesive material, which contains -NH-structure in the main chain, as a "reactive adhesive" to improve the electron and ion transport capabilities of lithium-ion batteries and enhance the Adhesive characteristics.
It improves the circulation performance and rate performance of lithium-ion batteries, enhances the bonding strength and conductivity of silicon negative electrodes, and solves the challenges of the battery in terms of high energy density and long cycle life.
Smart Images

Figure CN119463794A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of lithium ion batteries, and in particular to a novel adhesive based on polyimide (PI), specifically a fluorine-containing soluble polyimide adhesive specially used for lithium batteries, and a preparation method and application thereof. Background Art
[0002] Lithium-ion batteries have become the main power source of choice for electric vehicles, portable electronic devices, and energy storage systems due to their high energy density, long cycle life, and high power density. However, as the requirements for battery performance in these applications continue to increase, the energy density of current lithium-ion batteries has approached its theoretical limit. In order to further improve the energy density and performance of batteries, researchers are constantly exploring new high-capacity electrode materials.
[0003] At present, the negative electrode material of commercial lithium-ion batteries is mainly graphite. Graphite has good conductivity and stable cycle performance, but its theoretical specific capacity is only 372mAh / g, which is difficult to meet the needs of future high-energy density batteries. In contrast, silicon (Si) as a negative electrode material has an extremely high theoretical specific capacity (about 4200mAh / g), which is more than ten times that of graphite. In addition, silicon reserves are abundant and low in cost, so it is considered to be an ideal negative electrode material for the next generation of high-energy density lithium-ion batteries.
[0004] Although silicon anodes have significant advantages, they still face a series of challenges in practical applications. The main problem is that silicon will expand and shrink by more than 300% during the insertion and extraction of lithium ions. This significant volume change can lead to silicon particle breakage, electrode structure damage, and adhesion failure with the current collector, which in turn leads to rapid capacity decay and shortened cycle life. In addition, an unstable solid electrolyte interface (SEI) film is easily formed on the silicon surface, further reducing battery performance.
[0005] In order to solve the above problems, researchers have proposed a variety of strategies, such as nanostructure design, composite material preparation, and the development of high-performance adhesives. Among them, adhesives play a vital role in the electrode structure. They are not only used to bond active materials and conductive agents, but also provide certain mechanical support and buffering to cope with the volume changes of electrode materials during the cycle. Adhesives are key materials for preparing electrodes. Their main function is to bond various particles together and tightly bond them to metal foil. A good adhesive is not only conducive to improving the energy density of the battery, but also has a significant effect on reducing the internal resistance of the battery, and has an important influence on the electrochemical properties of the battery.
[0006] Traditional lithium-ion battery adhesives such as polyvinylidene fluoride (PVDF) have excellent chemical and electrochemical stability, but the mechanical properties of PVDF adhesive materials are insufficient, and the adhesion to the negative electrode is poor. The repeated volume changes of the electrode material during the cycle process can easily cause the electrode sheet to be pulverized, peeled off, and other damages, thereby affecting the battery performance. Therefore, improving and enhancing the negative electrode adhesion is helpful to obtain stable battery performance.
[0007] Polyimide (PI) is a polymer material with excellent performance, widely used in aerospace, electrical and electronic, chemical and other fields. The aromatic ring and imide group in the molecular structure of polyimide give it excellent mechanical strength, heat resistance and chemical stability, but the traditional polyimide material for preparing batteries also has the problem of insufficient ion transport and electronic conductivity, and the structure of polyimide material also directly affects the adhesion of electrodes. Summary of the invention
[0008] The present invention aims at the technical problems encountered in the practical application of high energy density lithium ion batteries, and designs a fluorine-containing soluble polyimide (PI) adhesive material. The main chain of the adhesive material contains -NH- structure, which belongs to the "reactive adhesive" with electron transfer interaction between the active material. The electrode material prepared by using the fluorine-containing soluble polyimide adhesive material has low impedance and high bonding properties, and the assembled lithium battery shows a higher rate. It is an effective solution for silicon negative electrode adhesive with high stability, high capacity and suitable for large-scale production.
[0009] The first object of the present invention is to provide a fluorine-containing soluble polyimide adhesive for lithium batteries, wherein the fluorine-containing polyimide is prepared by reacting a dianhydride with a diamine, wherein the dianhydride includes 4,4'-hexafluoroisopropylphthalic anhydride (6FDA), and the diamine includes 4,4'-diaminodiphenylamine (NDA). The structural formula of the fluorine-containing polyimide 6FDA-NDA is as follows:
[0010]
[0011] Preferably, the dianhydride further comprises other dianhydrides, and the diamine further comprises other diamines.
[0012] More preferably, the other dianhydride is selected from one or more of 3,3',4,4'-biphenyltetracarboxylic dianhydride (BPDA), polyphthalic anhydride (PMDA), 4,4'-oxydiphthalic anhydride (ODPA) and 3,3,4,4-benzophenonetetracarboxylic dianhydride (BTDA).
[0013] More preferably, the other diamine is selected from one or more of 4,4'-diaminodiphenyl ether (ODA), p-phenylenediamine (PDA), and 2,2'-bis(trifluoromethyl)diaminobenzene (TFMB).
[0014] Preferably, the molar percentage of the fluorinated polyimide 6FDA-NDA structure is 70-100%.
[0015] Preferably, the adhesive further comprises an inorganic material, and the inorganic material is selected from inorganic fibers, preferably sepiolite fibers.
[0016] Further preferably, the mass ratio of the inorganic material to the fluorinated polyimide 6FDA-NDA is 1:8-12.
[0017] The second object of the present invention relates to a method for preparing the above-mentioned fluorine-containing soluble polyimide adhesive, the preparation method comprising the following steps:
[0018] (1) Adding 6FDA and NDA to a non-protonic polar solvent for polycondensation; or adding 6FDA, other dianhydrides, NDA, and other diamines to a non-protonic polar solvent for polycondensation;
[0019] (2) After the polymerization is completed, a catalyst and a dehydrating agent are added to react to obtain the product.
[0020] Preferably, the aprotic polar solvent in step (1) is selected from at least one of N,N-dimethylformamide, N-methylpyrrolidone and N,N-dimethylacetamide.
[0021] Preferably, the catalyst in step (2) is selected from at least one of pyridine, isoquinoline and picoline.
[0022] Preferably, the dehydrating agent in step (2) is selected from acetic anhydride.
[0023] In some embodiments, the method for preparing the fluorine-containing soluble polyimide adhesive provided by the present invention comprises the following specific steps:
[0024] 1) mixing a dianhydride monomer containing fluorine in the main chain and a diamine monomer dissolved in an aprotic strong polar solvent in a round-bottom flask, and stirring the mixture at a certain speed to carry out polymerization reaction;
[0025] 2) adding acetic anhydride and pyridine to the solvent after the polymerization is completed, and continuing to stir the reaction;
[0026] 3) The obtained sol is poured into anhydrous ethanol for precipitation to obtain a fluorine-containing soluble polyimide.
[0027] In some preferred embodiments, the main chain fluorine-containing dianhydride monomer in step 1) is selected from 4,4-hexafluoroisopropylphthalic anhydride (6FDA), the diamine monomer is selected from 4,4'-diaminodiphenylamine (NDA), and the aprotic strong polar solvent can be selected from at least one of N,N-dimethylformamide (DMF), N-methylpyrrolidone (NMP) and N,N-dimethylacetamide (DMAc), preferably DMAc.
[0028] In some preferred embodiments, the reaction temperature in step 1) is room temperature, preferably 25°C; the reaction time is 12-24h, preferably 16h; the rotation speed is 50-300r / min, preferably 280r / min. The reaction time in step 2) is 12-24h, preferably 16h; the rotation speed is 50-300r / min, preferably 280r / min.
[0029] In some preferred embodiments, the dianhydride in step 1) includes 4,4'-hexafluoroisopropylphthalic anhydride (6FDA) and 3,3,4,4-benzophenonetetracarboxylic dianhydride (BTDA), and the diamine includes 4,4'-diaminodiphenylamine (NDA) and 4,4'-diaminodiphenyl ether (ODA), wherein the molar percentage of the 6FDA-NDA polyimide structure is 70-100%.
[0030] In some preferred embodiments, the dianhydride in step 1) includes 4,4'-hexafluoroisopropylphthalic anhydride (6FDA) and 4,4'-oxydiphthalic anhydride (ODPA), and the diamine includes 4,4'-diaminodiphenylamine (NDA) and 2,2'-bis(trifluoromethyl)diamino (TFMB), wherein the molar percentage of the 6FDA-NDA polyimide structure is 70-100%.
[0031] The third object of the present invention relates to the application of the above-mentioned fluorine-containing soluble polyimide adhesive in the field of lithium-ion batteries, mainly in silicon negative electrode lithium-ion batteries.
[0032] Compared with the prior art, the present invention has the following beneficial effects: (1) The fluorine-containing soluble polyimide adhesive material of the present invention contains an amino (-NH-) structure and is a "reactive adhesive" that has electron transfer interaction with the active material. It not only has good bonding performance, but also can effectively promote the electron and ion transmission in lithium-ion batteries, thereby improving the cycle performance of silicon negative electrode lithium-ion batteries; (2) The fluorine-containing soluble polyimide adhesive of the present invention is used in lithium-ion batteries, especially silicon negative electrode lithium-ion batteries, and exhibits excellent rate performance and bonding performance, and has good industrial prospects. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] Figure 1This is the battery rate performance diagram of the prepared PI adhesive material. DETAILED DESCRIPTION
[0034] The following examples are used to illustrate the present invention, but are not intended to limit the scope of the present invention.
[0035] The methods are conventional methods unless otherwise specified. The materials are available from public commercial sources unless otherwise specified.
[0036] The performance evaluation method of the fluorine-containing soluble polyimide adhesive material obtained in the following examples is as follows:
[0037] The conductive performance evaluation method of polyimide adhesive material adopts the four-terminal method to measure resistance.
[0038] Electrochemical performance evaluation method of polyimide adhesive material: The rate performance test was measured using the Blue Electric Test System CT3002A, and the test conditions were 5 cycles of charge and discharge at current densities of 0.1C, 0.5C, 1C, 2C, and 5C, respectively.
[0039] Evaluation method for the peeling performance of polyimide adhesive materials: stick a 2cm wide 3M tape on the dried battery electrode, connect the other end of the tape to a tensile testing machine, so that the tape peels off the electrode slurry at an angle of 180°, and the force of the tensile testing machine gradually increases from 0N until the tape completely falls off the electrode, and record the peak force during the peeling process.
[0040] Example 1: Preparation of polyimide (PI) adhesive material using 6FDA and NDA
[0041] Weigh 9.9625g of 4,4'-diaminodiphenylamine (NDA) and place it in a round-bottom flask. Add an appropriate amount of DMAc solvent to dissolve it under stirring. Weigh 22.21g of 4,4-hexafluoroisopropylphthalic anhydride (6FDA) and add it to the above device. The stirring paddle speed is 280r / min and the reaction time is 16h. Subsequently, acetic anhydride and pyridine are added to the device, the speed setting remains unchanged, and stirring is continued for 16h. After the reaction is completed, the obtained sol is poured into anhydrous ethanol solution for precipitation to obtain a fluorine-containing soluble PI adhesive material.
[0042] Take the prepared PI adhesive material and dissolve it in the NMP solution to prepare a solution with a PI content of 0.2g / mL. According to the ratio of active material (Si / C, reversible specific capacity 650mAh / g): conductive agent (Super P): adhesive (PI) = 5:4:1, take an appropriate amount and put it in a 20mL small glass bottle, stir it magnetically for 10h, and prepare the electrode slurry. Then, use a 150-micron-thick scraper to evenly coat the slurry on the carbon-coated copper foil, put it in a positive vacuum oven and heat it at 120°C for 10h to obtain a dry electrode. Then, assemble the battery in a glove box and test the rate performance.
[0043] Rate performance as attached Figure 1 As shown;
[0044] The peel strength properties of the prepared PI adhesive material are shown in Table 1, and the electrical conductivity properties are shown in Table 2.
[0045] Example 2: Doping sepiolite fibers in the preparation of PI adhesive materials using 6FDA and NDA
[0046] The preparation method of the PI adhesive material in Example 2 is the same as that in Example 1, except that after the PI material is dissolved in the NMP solution, 10% of the mass of sepiolite fiber of PI is added thereto, and the subsequent steps of preparing the electrode sheet and assembling the battery are the same.
[0047] Rate performance as attached Figure 1 As shown;
[0048] The peel strength properties of the prepared PI adhesive material are shown in Table 1, and the electrical conductivity properties are shown in Table 2.
[0049] Example 3: Preparation of polyimide (PI) adhesive material using 6FDA, BTDA, NDA and ODA
[0050] Weigh 9.9625g of 4,4'-diaminodiphenylamine (NDA) and 10.0118g of 4,4'-diaminodiphenyl ether (ODA) in a round-bottom flask, add an appropriate amount of DMAc solvent to dissolve it under stirring, weigh 22.21g of 4,4-hexafluoroisopropylphthalic anhydride (6FDA) and 32.223g of 3,3',4,4'-dibenzophenone tetracarboxylic dianhydride (BTDA) and add them to the above device, the stirring paddle speed is 280r / min, and the reaction time is 16h. Subsequently, acetic anhydride and pyridine are added to the device, the speed setting remains unchanged, and stirring is continued for 16h. After the reaction is completed, the obtained sol is poured into anhydrous ethanol solution for precipitation to obtain a fluorine-containing soluble PI adhesive material.
[0051] Take the prepared PI adhesive material and dissolve it in the NMP solution to prepare a solution with a PI content of 0.2g / mL. According to the ratio of active material (Si / C, reversible specific capacity 650mAh / g): conductive agent (Super P): adhesive (PI) = 5:4:1, take an appropriate amount and put it in a 20mL small glass bottle, stir it magnetically for 10h, and prepare the electrode slurry. Then, use a 150-micron-thick scraper to evenly coat the slurry on the carbon-coated copper foil, put it in a positive vacuum oven and heat it at 120°C for 10h to obtain a dry electrode. Then, assemble the battery in a glove box and test the rate performance.
[0052] The peel strength properties of the prepared PI adhesive material are shown in Table 1, and the electrical conductivity properties are shown in Table 2.
[0053] Example 4: Doping sepiolite fibers in polyimide (PI) adhesive materials prepared from 6FDA, BTDA, NDA and ODA
[0054] The preparation method of the PI adhesive material in Example 4 is the same as that in Example 3, except that after the PI material is dissolved in the NMP solution, 10% of the mass of sepiolite fiber of PI is added thereto, and the subsequent steps of preparing the electrode sheet and assembling the battery are the same.
[0055] The peel strength properties of the prepared PI adhesive material are shown in Table 1, and the electrical conductivity properties are shown in Table 2.
[0056] Example 5: Preparation of polyimide (PI) adhesive material using 6FDA, ODPA, NDA and TFMB
[0057] Weigh 9.9625g of 4,4'-diaminodiphenylamine (NDA) and 16.0115g of 2,2'-di(trifluoromethyl)diamino (TFMB) in a round-bottom flask, add an appropriate amount of DMAc solvent to dissolve it under stirring, weigh 22.21g of 4,4-hexafluoroisopropylphthalic anhydride (6FDA) and 15.5105g of 4,4'oxydiphthalic anhydride (ODPA) and add them to the above device, the stirring paddle speed is 280r / min, and the reaction time is 16h. Subsequently, acetic anhydride and pyridine are added to the device, the speed setting remains unchanged, and stirring is continued for 16h. After the reaction is completed, the obtained sol is poured into anhydrous ethanol solution for precipitation to obtain a fluorine-containing soluble PI adhesive material.
[0058] Take the prepared PI adhesive material and dissolve it in the NMP solution to prepare a solution with a PI content of 0.2g / mL. According to the ratio of active material (Si / C, reversible specific capacity 650mAh / g): conductive agent (Super P): adhesive (PI) = 5:4:1, take an appropriate amount and put it in a 20mL small glass bottle, stir it magnetically for 10h, and prepare the electrode slurry. Then, use a 150-micron-thick scraper to evenly coat the slurry on the carbon-coated copper foil, put it in a positive vacuum oven and heat it at 120°C for 10h to obtain a dry electrode. Then, assemble the battery in a glove box and test the rate performance.
[0059] The peel strength properties of the prepared PI adhesive material are shown in Table 1, and the electrical conductivity properties are shown in Table 2.
[0060] Example 6: Doping sepiolite fibers in polyimide (PI) adhesive materials prepared from 6FDA, ODPA, NDA and TFMB
[0061] The preparation method of the PI adhesive material in Example 6 is the same as that in Example 5, except that after the PI material is dissolved in the NMP solution, 10% of the mass of sepiolite fiber of PI is added thereto, and the subsequent steps of preparing the electrode sheet and assembling the battery are the same.
[0062] The peel strength properties of the prepared PI adhesive material are shown in Table 1, and the electrical conductivity properties are shown in Table 2.
[0063] Comparative Example 1: Polyvinylidene fluoride (PVDF) as a lithium-ion battery adhesive
[0064] The polyvinylidene fluoride (PVDF) in Comparative Example 1 is a product produced by Arkema, France. PVDF was dissolved in NMP solution to prepare a solution with a PVDF content of 0.2 g / mL. According to the ratio of active material (Si / C, reversible specific capacity 650 mAh / g): conductive agent (Super P): adhesive (PVDF) = 5:4:1, an appropriate amount was placed in a 20 mL small glass bottle, and magnetic stirring was performed for 10 hours to prepare an electrode slurry, and then the slurry was evenly coated on a carbon-coated copper foil with a 150 micron thick scraper, and placed in a positive vacuum oven and heated at 120°C for 10 hours to obtain a dry electrode sheet, and then the battery was assembled in a glove box to test the rate performance.
[0065] Rate performance as attached Figure 1 As shown;
[0066] The peel strength properties of the prepared adhesive material are shown in Table 1, and the electrical conductivity properties are shown in Table 2.
[0067] Comparative Example 2: Carboxymethyl cellulose (CMC) as a lithium-ion battery binder
[0068] The carboxymethyl cellulose (CMC) in Comparative Example 2 was purchased from Kejingxing Technology Co., Ltd. (Shenzhen). CMC was dissolved in deionized water to prepare a solution with a CMC content of 0.2 g / mL. According to the ratio of active material (Si / C, reversible specific capacity 650 mAh / g): conductive agent (Super P): adhesive (CMC) = 5:4:1, an appropriate amount was placed in a 20 mL small glass bottle, and magnetically stirred for 10 hours to prepare an electrode slurry. The slurry was then evenly coated on a carbon-coated copper foil with a 150-micron-thick scraper, placed in a positive vacuum oven and heated at 120°C for 10 hours to obtain a dry electrode sheet, and then the battery was assembled in a glove box to test the rate performance.
[0069] Rate performance as attached Figure 1 As shown;
[0070] The peel strength properties of the prepared adhesive material are shown in Table 1, and the electrical conductivity properties are shown in Table 2.
[0071] Table 1: PI adhesive material composition and pole piece peel strength performance
[0072]
[0073] Table 2: Conductive properties of PI adhesive materials
[0074]
[0075]
[0076] From the data in Table 1, it can be seen that compared with Comparative Examples 1 and 2, Examples 1 and 2 using the fluorine-containing soluble polyimide adhesive of the present invention as the adhesive material have higher bonding strength. At the same time, the bonding effect of Example 2 doped with a small amount of sepiolite fiber is better than that of Example 1. As can be seen from Table 2, the fluorine-containing soluble polyimide adhesive materials of Examples 1-6 of the present invention have higher electrical conductivity. Figure 1 It can be seen from the data that the silicon negative electrode lithium ion battery using the fluorine-containing soluble polyimide of the present invention as a binder has a better rate performance, and the battery performance of the PI doped with sepiolite fiber is also relatively improved.
[0077] It can be seen that the fluorine-containing soluble polyimide adhesive material proposed in the present invention has excellent rate performance in silicon negative electrode lithium ion batteries, is simple to operate, and does not produce by-products. This implementation scheme has good industrial prospects.
[0078] Finally, the method of the present invention is only a preferred embodiment and is not intended to limit the protection scope of the present invention. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.
Claims
1. A fluorine-containing soluble polyimide adhesive for lithium batteries, characterized in that: The fluorinated polyimide is prepared by reacting a dianhydride with a diamine, wherein the dianhydride includes 4,4'-hexafluoroisopropylphthalic anhydride, and the diamine includes 4,4'-diaminodiphenylamine. The structural formula of the fluorinated polyimide 6FDA-NDA is as follows:
2. The fluorinated polyimide adhesive according to claim 1, characterized in that: The dianhydride also includes other dianhydrides, and the diamine also includes other diamines. The other dianhydrides are selected from at least one of 3,3',4,4'-biphenyltetracarboxylic dianhydride, polyphthalic anhydride, 4,4'-oxydiphthalic anhydride and 3,3,4,4-benzophenonetetracarboxylic dianhydride; the other diamines are selected from at least one of 4,4'-diaminodiphenyl ether, p-phenylenediamine and 2,2'-bis(trifluoromethyl)diamino.
3. The fluorinated polyimide adhesive according to claim 1 or 2, characterized in that: The molar percentage of the fluorine-containing polyimide structure is 70-100%.
4. The fluorinated polyimide adhesive according to claim 1 or 2, characterized in that: The adhesive further comprises an inorganic material, and the inorganic material is selected from inorganic fibers, preferably sepiolite fibers.
5. A method for preparing the fluorinated polyimide adhesive according to any one of claims 1 to 4, the method comprising the following steps: (1) Add 4,4'-hexafluoroisopropylphthalic anhydride and 4,4'-diaminodiphenylamine to a non-protonic polar solvent for polycondensation or In a non-protonic polar solvent, 4,4'-hexafluoroisopropylphthalic anhydride, other dianhydrides, 4,4'-diaminodiphenylamine, and other diamines are added to carry out polycondensation reaction; (2) After the polymerization is completed, a catalyst and a dehydrating agent are added to react to obtain the product.
6. The preparation method according to claim 5, characterized in that: The aprotic polar solvent in step (1) is selected from at least one of N,N-dimethylformamide, N-methylpyrrolidone and N,N-dimethylacetamide.
7. The preparation method according to claim 5, characterized in that: The catalyst in step (2) is selected from at least one of pyridine, isoquinoline and picoline.
8. The preparation method according to claim 5, characterized in that: The dehydrating agent in step (2) is selected from acetic anhydride.
9. The preparation method according to claim 5, characterized in that: In step (1), the other dianhydride is 3,3,4,4-benzophenonetetracarboxylic dianhydride or 4,4'-oxydiphthalic anhydride, and the other diamine is 4,4'-diaminodiphenyl ether or 2,2'-bis(trifluoromethyl)diamino, wherein the polyimide 6FDA-NDA structure content is 70-100 mol%.
10. Use of the fluorinated polyimide adhesive according to any one of claims 1 to 4 or the fluorinated polyimide adhesive prepared according to any one of claims 5 to 9 in the field of lithium-ion batteries, characterized in that: The lithium ion battery is a silicon negative electrode lithium ion battery.
Citation Information
Cited By
Fluorine-containing soluble polyimide adhesive special for lithium ion battery and preparation method and application of fluorine-containing soluble polyimide adhesive
CN120137588A
Positive electrode, preparation method and battery
CN120637384A
A positive electrode, a production method, and a battery
CN120637384B
Lithium secondary battery cell, electrical apparatus, and method for preparing lithium secondary battery
WO2026179427A1